Digital Transformation and E-Commerce Growth: Impact on Consumer Behavior and SMEs - Annisa Wahdiniawati, Siti; Apriani, Ari; Alvin Orlando, Arthur (Dinasti Publisher, 2024)
This study investigates the factors influencing online shopping interest and consumer trust in e-commerce platforms, focusing on the Shopee platform. Through surveys and interviews with MSME players, the study reveals that perceived risk, particularly psychological risk, does not significantly affect online shopping interest or consumer trust. Conversely, perceived usefulness, especially in terms of time-saving, positively and significantly influences both online shopping interest and trust. While electronic word-of-mouth (e-WOM) does not impact online shopping interest, it positively and substantially affects trust. Trust mediates the relationship between perceived usefulness and online shopping interest, as well as between e-WOM and online shopping interest. These findings highlight the complexity of factors influencing online shopping behavior and underscore trust's critical role in mediating these relationships. The implications suggest that e-commerce platforms should enhance perceived usefulness and consumer trust through improved service and product quality, and active customer engagement. Strategies include improving customer service quality, incentivizing positive reviews, and ensuring transparency in return policies and data privacy. MSME players can leverage these insights to develop more effective marketing strategies, boost consumer engagement, and strengthen consumer relationships in the e-commerce environment.